Support and assist: approaches to mentoring in a yearlong teacher residency. Issue 1 (7th March 2016) - Roegman, Rachel; Reagan, Emilie Mitescu; Goodwin, A. Lin; Yu, Julia
Abstract : Purpose: – The purpose of this paper is to examine mentor teachers' approaches to mentoring preservice teachers in a yearlong teacher residency program (TRP). Design/methodology/approach: – This multiple-methods study examined 15 mentor teachers' approaches over the course of a year in an urban TRP through the lens of Wang and Odell's (2002) framework for mentoring. Data sources included mentors' self-assessments over three points in time across one academic year. These self-assessments included numerical ratings of practice (quantitative) as well as open-ended rationales and goal setting (qualitative). Findings: – Mentors predominately provided support and technical assistance to the residents learning to teach, drawing on humanistic, and situated apprentice perspectives on mentoring. They worked to develop residents' self-confidence and exposed residents to a range of practices and school contexts. Glimmers of a more critical constructive approach were apparent in some mentors' discussions of reflection and collaboration. Research limitations/implications: – This study informs the work of teacher education programs as they develop mentoring structures that align with program visions, expand notions of mentoring, and consider the many roles of a mentor teacher. Originality/value: – Increased emphasis on clinical experiences for preservice teachers highlights the need to attend to the practices of the mentor teachers with whom they work. These mentors, as field-based teacher educators, play a critical role in teacher education, and teacher education programs need to support their professional development as mentors. Understanding mentors' approaches to mentoring is necessary in order to provide this support.